Effect of Uzarin Isolated from Calotropis procera on Blood Electrolytes and Cardiac Related Enzymes - Nagy Morsy
Background: Cardiac glycosides are known to be one of the most important drugs that extracted from medicinal plants. Cardiac glycosides have been used as a medicine for a long time with congestive heart failure. Objectives: In this study, we aim to investigate the biochemical changes happened in male rats by Uzarin, the cardiac glycoside isolated from Calotropis procera, to monitor the biochemical changes caused by cardiac glycosides in the long-term therapy or the overdose intake as well. Materials and Methods: Uzarin is isolated and purified from Calotropis procera by chromatographic methods. Uzarin structure was determined by 2 D NMR techniques. Determination of Serum Electrolytes Concentrations and cardiac related enzymes were done using biochemical methods. Results: This study may reflect the changes in serum electrolytes and cardiac related enzymes that happen with cardiac glycosides-dependent patients. Conclusion: Uzarin could significantly decrease K, Na, Ca, Mg and Cl levels 24 hr after injection. In serum, Creatine Kinase (CK) and Lactate Dehydrogenase (LDH) as well as gc(B-Glutamyl Transferase (GGT) activities were highly increased.s